Exploring non-central nervous system cancer survivors access, acceptability and expectations regarding interventions for cognitive complaints [abstract] - Oliveira, Ana Filipa (2023)
BACKGROUND-AIM: Several non-pharmacological interventions have been explored for non-central nervous system (CNS) cancer survivors reporting cancer-related cognitive impairment (CRCI). Cognitive rehabilitation (CR) is considered the first-line intervention for CRCI. This study aimed to explore access to and acceptability of CRCI interventions and explore expectations regarding CR. METHODS: The sample included 135 Portuguese non-CNS cancer survivors reporting cognitive complaints (Mage547.4, SD59.4 years). Participants were recruited through social networks and replied to an online survey on previous/current access to CRCI interventions, acceptability of these interventions, and expectations about CR. RESULTS: Most of the participants were women and breast cancer survivors. Only 12 participants reported receiving or having already received CRCI support, mostly psychological support. For those who have never received it, the main reported reason was not knowing interventions are available/how to access them. Cognitive evaluation, psychological support, physical activity, and CR were considered the most acceptable interventions. Almost all participants reported being interested in having access to CR and considered that this type of intervention would be efficient and useful to deal with CRCI. CONCLUSIONS: The findings show that Portuguese non-CNS cancer survivors rarely have support to manage CRCI, although they are interested in having access to interventions, namely CR. This landscape stresses the need to develop and make available cognitive support and CR programs to this population, who frequently reports CRCI.